Chronic levamisole exposure in male rats alters sexual behavior and induces apoptosis in the testis - Yardimci, Ahmet; Mulayim, Sefa; Kaya Tektemur, Nalan; Tektemur, Ahmet; Erensoy, Ahmet (Taylor & Francis Ltd, 2024)
Levamisole is an anti-helminthic drug developed and introduced in veterinary medicine, and it has been used more frequently after the inclusion of its usage in human medicine regarding disorders with immunomodulatory properties. In recent years, it has started to attract attention since it has beneficial effects on the treatment of COVID-19 due to its immunomodulatory properties. To investigate the effects of levamisole on sexual behavior and the reproductive system in male rats, two groups were formed the vehicle (n = 10) and levamisole (n = 10) groups. The vehicle group was given purified water whereas the levamisole group was administered with levamisole (2 mg/kg) by oral gavage daily for 4 weeks. Levamisole treatment significantly increased the mount latency (ML, P < 0.001) as well as the intromission latency (IL, P < 0.01). It also significantly prolonged postejaculatory interval (PEI, P < 0.01), decreased copulatory rate (CR, P < 0.05), and sexual activity index (SAI, P < 0.05). It significantly decreased serum monoamine oxidase A (MAO-A) levels (P < 0.05). Additionally, levamisole induced disorganizations of germinal epithelial cells of seminiferous tubules, congestion, edema in the interstitial area, and metaphase arrest in some spermatocytes (P < 0.001), and it significantly increased the immunohistochemical expressions of apoptotic Bax and cytochrome c, which is crucial proapoptotic protein, in the testis (P < 0.001). Also, levamisole significantly upregulated the mRNA levels of the apoptosis-related key regulatory genes, including Bax (Bcl-2-associated X protein, P = 0.05) and Bax/Bcl-2 ratio (P < 0.01) in testis. The current research is the first to show that levamisole may decrease sexual performance, potency, sexual motivation, and libido and induce apoptosis in the testis.
Keywords: Levamisole; MAO-A; sexual behavior; potency; apoptosis